Sleep, Sleepiness, and Fatigue on Board Faroese Fishing Vessels - Abrahamsen A; Weihe P; Debes F; van Leeuwen WMA (Dove Medical Press, 2022)
Annbjørg Abrahamsen,1,2 Pál Weihe,1,2 Fróði Debes,1 Wessel MA van Leeuwen3 1Department of Occupational Medicine and Public Health, The Faroese Hospital System, Tórshavn, Faroe Islands; 2The University of Faroe Islands, Faculty of Health Sciences, Tórshavn, Faroe Islands; 3Stockholm University, Department of Psychology, Stress Research Institute, Stockholm, SwedenCorrespondence: Wessel MA van Leeuwen, Stockholm University, Department of Psychology, Stress Research Institute, Stockholm, 10691, Sweden, Tel +46 08-553 789 17, Email wessel.vleeuwen@su.sePurpose: Faroese fishers have four times more accidents than workers on land. The aim was to understand fishers’ fatigue better and how their work and sleep patterns influenced their sleepiness levels and cognitive performance.Materials and Methods: A total of 157 Faroese fishers wore wrist-worn actigraphs at sea and one week on land and filled in sleep and sleepiness diaries during the trip. Furthermore, a 3-minute simple reaction time (SRT) test was completed at the beginning and end of the trip. The ship’s movement and noise were also logged. The actiwatch results were analysed with mixed methods repeated measures. The sleepiness registrations and performance on the SRT-test were analysed with paired t-test. The ship movements (Pitch and roll) were divided into approximately three same-sized groups (lowest 1/3, medium 1/3, and highest 1/3) and compared against the Karolinska Sleepiness Scores (KSS ranging from 1– 9) ≥ 7 and physical tiredness (ranging from 1– 9) scores ≥ 7. Chi-square tests were used to determine the significance of these differences. Mean sleepiness scores at sea, and the proportion of sleepiness scores ≥ 7 were calculated, as well as sleepiness scores as a function of the time of day.Results: While at sea, fishers had more split sleep, slept less, and had lower sleep efficiency than onshore. Sleepiness was higher at the end of the trip, and cognitive decline was found. The number of major lapses was higher at the end of the trip, but with no ...